Penegakan Hukum terhadap Tindak Pidana Penjualan Hasil Tambang Tanpa Izin di Indonesia (Studi Putusan Nomor 48/Pid.Sus/2023/Pn.Mntk) - Ratu Sheebakayla; Suwari Akhmaddhian (Savana, 2025)
The abundance of mining resources in Indonesia, besides having positive impacts, can also have negative impacts, such as triggering the practice of selling mining products without permits. This study aims to determine the regulation of criminal acts of selling mining products without permits and its implementation in cases of illegal mining in West Bangka Regency based on Decision Number 48/Pid.Sus/2023/Pn.Mntk. The research method used in this research is the library research method. The results show that based on Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining, every mining activity is required to have a permit. Mining without permits causes significant losses to the state and society. In conclusion, the crime of selling mining products without a permit is regulated in Article 161 of Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining where the perpetrator is threatened with a maximum imprisonment of 5 (five) years and a maximum fine of IDR 100,000,000,000.00 (one hundred billion rupiah). The implementation of the regulation of the practice of selling mining products without a permit in Decision Number 48 / Pid.Sus / 2023 / Pn.Mntk is shown by the imposition of a criminal sentence on the Defendant YF with a prison sentence of 4 (four) months and a fine of IDR 1,000,000 subsidiary 2 (two) months. The government should carry out strict supervision in the mining sector to prevent and overcome the practice of selling mining products and needs to hold socialization regarding the negative impacts of illegal mining.